If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 4)(x + -2) = 40 Reorder the terms: (4 + X)(x + -2) = 40 Reorder the terms: (4 + X)(-2 + x) = 40 Multiply (4 + X) * (-2 + x) (4(-2 + x) + X(-2 + x)) = 40 ((-2 * 4 + x * 4) + X(-2 + x)) = 40 ((-8 + 4x) + X(-2 + x)) = 40 (-8 + 4x + (-2 * X + x * X)) = 40 (-8 + 4x + (-2X + xX)) = 40 Reorder the terms: (-8 + -2X + 4x + xX) = 40 (-8 + -2X + 4x + xX) = 40 Solving -8 + -2X + 4x + xX = 40 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '8' to each side of the equation. -8 + -2X + 4x + 8 + xX = 40 + 8 Reorder the terms: -8 + 8 + -2X + 4x + xX = 40 + 8 Combine like terms: -8 + 8 = 0 0 + -2X + 4x + xX = 40 + 8 -2X + 4x + xX = 40 + 8 Combine like terms: 40 + 8 = 48 -2X + 4x + xX = 48 Add '-4x' to each side of the equation. -2X + 4x + -4x + xX = 48 + -4x Combine like terms: 4x + -4x = 0 -2X + 0 + xX = 48 + -4x -2X + xX = 48 + -4x Reorder the terms: -48 + -2X + 4x + xX = 48 + -4x + -48 + 4x Reorder the terms: -48 + -2X + 4x + xX = 48 + -48 + -4x + 4x Combine like terms: 48 + -48 = 0 -48 + -2X + 4x + xX = 0 + -4x + 4x -48 + -2X + 4x + xX = -4x + 4x Combine like terms: -4x + 4x = 0 -48 + -2X + 4x + xX = 0 The solution to this equation could not be determined.
| 5g+(-7)=-52 | | xa+5x-4=10 | | 4x(x+2)=6x | | -2.3q+16=-5g-38 | | y-4z=-42 | | 0=16t^2+104+56 | | -5x/3x= | | 4x^2-5y-100=0graph | | 4x^2y^2-2y^4-8xy^3+9x^3y+6y^4-2xy^3-3x^4+x^2y^2-3x^4= | | Y-23/3=-11 | | 4x^2-5y-100=0 | | C+3=4c-13 | | Y-20/3=-11 | | 48-(-4x)=7 | | 16x+9-17=(-3x)+7x | | 12-4-2= | | 6m+5(m+1)=26 | | r(x)=14 | | 7/16x=28 | | R*9/2=27 | | 5y=x+45 | | x^2-4x+5=-x^2+4x-1 | | W/1.02/3=-5 | | -21m+1=-7m+1 | | 4=(3x+1)-(16x-1) | | 2.3x+.5x=100 | | 20-3n=20-5n | | 3(-7x+8)=-165 | | x^2-144=169 | | 2(5x-9)=52 | | 10x+2x=90 | | 5/q-3.75=26.25 |